Meningkatkan Keterampilan Literasi Informasi Guru dan Siswa Di Era Digital - Perdana, Fitri (PT. RANESS MEDIA RANCAGE, 2023)
Education is a very important factor. The aim of National Education is to educate the life of the nation and develop the Indonesian people as a whole, namely people who believe and are devoted to the Almighty and have noble character, have knowledge and skills, physical and spiritual health, a strong and independent personality and a sense of community responsibility. as well as nationality. In the current information age, a lot of information is scattered, so there is one skill that needs to be possessed, namely Information Literacy Skills, considering that there is a lot of information that is not of good quality. The method used is qualitative. Collecting data from observations, interviews and literature studies. Efforts to improve information literacy skills in Elementary Schools (SD) can be carried out with programs such as: Making and distributing educational posters, puzzle games, attaching literacy tree banners, decorating libraries. While increasing information literacy for teachers and parents, packaged in the form of Training from Lecturers in accordance with their fields, namely: Lecturers of the Library and Information Science Study Program provide material on Information Literacy Skills, Information Needs, how to find information from information sources, etc. Next Lecturer: Communication Management who provides material on the Impact of Social Media in the Digital Age. As a result, through programs or good practices implemented in the school, there is an increase in literacy skills in the school. Keywords: Literacy, Information, Teacher, Student, Digital Age, Elementary School, Good Practices